AKTIVITAS FORMULASI PESTISIDA NABATI PADA SIPUT SETENGAH TELANJANG Parmarion martensi (GASTROPODA: ARIOPHANTIDAE) - Sabina Sunarti Una; Sri Wahyuni (Agriculture Faculty of Flores University, 2019)
This study aims to determine the activity of plant-based pesticide formulations on martyred Parmarion semi-naked snails. The study conducted at the Laboratory of the Faculty of Agriculture, University of Flores, Sam Ratulangi Street, Ende Regency. The research was conducted from February to August 2019 using a Completely Randomized Design (CRD) with two stages of treatment. The first stage was testing the contact poison activity in 5 treatments namely P0 = Control, P1 = Dilution 1: 5, P2 = Dilution 1:10, P3 = Dilution 1:15, P4 = Pure extract. The second step is to test the stomach poison with five treatments namely R0 = Control, R1 = No immersion, R2 = Soak 10 minutes, R3 = Soak 20 minutes, R4 = Soak 30 minutes. All treatments are repeated five times so that they will get 25 units of experiments in every treatment. The results showed the concentration of vegetable pesticide extracts in contact poisons and stomach poisons the highest average mortality for contact poisons were found in P4 therapy with the highest mortality value of 68.00% and experienced the fastest death above 50.00% at 50.80 hours with single speed time is 0.55 hours. While the stomach poison in the R4 treatment is 66.66% with the time, the fastest mortality is above 50.00%, which is 55.40 hours with a speed of 0.57 hours per individual.